Peculiarities of distribution of unseeded species in crops of perennial grasses, depending on the composition of the grass mixture and the mode of use of the grass - Olifirovich, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The article investigated the species composition and dynamics of changes in the contamination of agrophytocenoses of perennial grasses, depending on the composition of the grass mixture and the mode of use of the grass stand. In the crops of perennial grasses, 34 weed species belonging to 12 botanical kind were found in the first three years of use of the grass stand. In the structure of weed infestation of perennial grasses, the species of the Astra kind of weeds dominated, which were represented by stanktis annual, dandelion, yarrow, field thistle.